Answer :

Since, f:R R and g:R R


fog:R R and gof:R R


f(x)=x2 + 8 and g(x)=3x3 + 1


So, gof(x)= g(f(x))


gof(x)= g(x2 + 8)


gof(x)= 3(x2 + 8)3 + 1


gof(x)= 3(x6 + 512 + 24x4 + 192x2) + 1


gof(x)= 3x6 + 72x4 + 576x2 + 1537


Similarly, fog(x)=f(g(x))


fog(x)= f(3x3 + 1)


fog(x)=(3x3 + 1)2 + 8


fog(x)=(9x6 + 1 + 6x3) + 8


fog(x)=9x6 + 6x3 + 9


So, gof(x) = 3x6 + 72x4 + 576x2 + 1537 and fog(x) = 9x6 + 6x3 + 9


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in theMathematics - Exemplar

Let f : [2, ∞) <sMathematics - Exemplar

Let f : N Mathematics - Exemplar

Fill in theMathematics - Exemplar

Let f :R →<Mathematics - Exemplar

Let f : [0, 1] <sMathematics - Exemplar

Which of the follMathematics - Exemplar